Integrasi Literasi Matematik dan Keterampilan Abad 21: Holistic Pendekatan Pendidikan Matematika di Kelas 5 SD 105329 Wonosari - Ria, Rut Rima; Handayani, Gati Sry; Gultom, Yosafat Maheswara; Oktaviani, An Nisa Nur (Indonesian Journal Publisher, 2024)
This study discusses the necessity of transforming the education system to meet the needs of the present era, particularly in the 21st century. 21st Century Education is defined as an education that integrates knowledge, attitudes, and skills with the mastery of information technology (IT). This shift redirects the focus from teacher-centered learning to student-centered learning. The main objective of this research is to examine how the integration of mathematical knowledge into mathematics instruction can be optimally achieved and to assess its impact on 21st-century mathematical skills. The research methodology employs a qualitative research method. The results of this study are expected to provide insights into the effectiveness of a comprehensive approach in enhancing mathematics education at the elementary level by training students to apply mathematical concepts learned in real-world situations while strengthening their skills for everyday life and the future.